Targeting the Mycobacterium tuberculosis Stringent Response as a Strategy for Shortening Tuberculosis Treatment - Danchik, Carina; Wang, Siqing; Karakousis, Petros C. (Frontiers in Microbiology, 2021)
The stringent response is well-conserved across bacterial species and is a key pathway involved both in bacterial survival and virulence and in the induction of antibiotic tolerance in Mycobacteria. It is mediated by the alarmone (p)ppGpp and the regulatory molecule inorganic polyphosphate in response to stress conditions such as nutrient starvation. Efforts to pharmacologically target various components of the stringent response have shown promise in modulating mycobacterial virulence and antibiotic tolerance. In this review, we summarize the current understanding of the stringent response and its role in virulence and tolerance in Mycobacteria, including evidence that targeting this pathway could have therapeutic benefit.